ANALISIS KELAYAKAN USAHA PETERNAKAN AYAM KAMPUNG DI DESA KUMBANG KECAMATAN MILA KABUPATEN PIDIE - Nadiya -; Aprilizar - (Jurnal Ilmiah Manajemen Muhammadiyah Aceh, 2011)
Local chicken farms is an effort to increase farmer income and create jobs, especially in rural areas. The aim of the study is to determine the magnitude of farmers income obtained from local chicken farms and find out the feasibility for chicken farming viewed from several aspects, among others market and marketing aspects, technical/operational aspects, management and financial aspects.Issue raised in the study Â is whether the chicken farming can increase income of farmers and whether it is feasible to run in the area where the study is conducted .Research was conducted in Kumbang Village of Mila Pidie district, Aceh. Simple random sampling is deployed to as many as 33 households from 133 in the village.The results of the study exhibit that local chicken farms can increase farmer income by Rp283.200, -/year for a family with 10 chickens. in terms of feasibility, local chicken farming is quite feasible to be implemented and developed examining market and marketing aspects. While it is not feasible in terms of technical aspects/operational and management aspects, it is quite feasible from the financial aspect as the financial analysis shows the R / C 1 that is 1.29 and is lower than 1 that is 0.77 which means the rate of return is under one year.Â  The capital used is very effective as evidenced by the value of a ROI of 129% which means benefit is greater than capital within one year of production.Based on the results of this study, local chicken farmers in Kumbang Village have to learn the procedure for raising local chicken with respect to the feasibility of the cage, feed quality, disease control and deploy good management to increase the income.Â